Melhorar para não mudar: ferrovia, intervenções urbanas e seu impacto social em Ouro Preto-MG, 1885-1897 - Mantovani, André Luiz (2007)
This work intends to analyze some of the impacts provoked by the railway, when she started to do part of the urban space of Ouro Preto and of the people s life that they resided there in the end of the 19th century. It tries to investigate the perception that groups of the Minas and Ouro Preto s elite possessed of this technology, as well as its expectations around its installation. After the Proclamation of the Republic, in 1889, the intention of transferring the capital of Minas Gerais of Ouro Preto for another area of the state won force. One of the arguments that would justify that measured it was the fact of the urban space of the city non to correspond with the model of the new times, not having means of improving it. The ligation of Ouro Preto the other parts of the state and to the city of Rio de Janeiro, it was one of the alternatives takings to avoid the change. Another strategy went to accomplishment of improvements in the urban mesh, tends in view the rail extension. The appearance of new daily experiences provided by the railway will also be observed, such as the easiness of people s circulation, information, goods and even diseases